2015
DOI: 10.1080/15299732.2015.1019175
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Traumatic Experiences, Dissociative Symptoms, and Dissociative Disorder Comorbidity Among Patients With Panic Disorder: A Preliminary Study

Abstract: This study assessed childhood trauma history, dissociative symptoms, and dissociative disorder comorbidity in patients with panic disorder (PD). A total of 92 psychotropic drug-naive patients with PD, recruited from outpatient clinics in the psychiatry department of a Turkish hospital, were involved in the study. Participants were assessed using the Structured Clinical Interview for DSM-IV Dissociative Disorders (SCID-D), Dissociation Questionnaire, Panic and Agoraphobia Scale, Panic Disorder Severity Scale, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
5
0
2
Order By: Relevance
“…The strongest association was observed with Childhood Emotional Abuse. An analysis of the results of the study confirmed the relationship between childhood experiences of emotional abuse and severity of panic disorder on the one hand and dissociative disorders, on the other [8].…”
Section: Dissociative Amnesiasupporting
confidence: 63%
See 1 more Smart Citation
“…The strongest association was observed with Childhood Emotional Abuse. An analysis of the results of the study confirmed the relationship between childhood experiences of emotional abuse and severity of panic disorder on the one hand and dissociative disorders, on the other [8].…”
Section: Dissociative Amnesiasupporting
confidence: 63%
“…Among the causative factors, there is also severe psychological trauma that may occur as a result of a direct threat to health or life [1]. The literature most frequently mentions traumatic experiences from early childhood [8], a dramatic loss of loved ones [9], violence [10], sexual abuse, catastrophes, war, natural disasters, traumatic experiences associated with pregnancy and the perinatal period [6], and protracted interpersonal and intrapsychic problems. [7,11,12,13,14,15].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…In the study by Pastucha et al .,[ 6 ] patients with panic disorder had similar DES scores when compared to healthy controls, but they had more frequent severe dissociative states and level of dissociation correlated with severity of anxiety symptoms. In another study,[ 2 ] 19% of patients with panic disorder had the comorbid dissociative disorder and patients with a high degree of dissociative symptoms and dissociative disorder comorbidity had more severe panic symptoms. The wide variability in the DES scores in panic disorder can probably be explained by a difference in the conceptualization of dissociation as comprising only of depersonalization-derealization during panic attacks or more broadly as disturbances in integrity of memory, cognition, and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Dissociative experiences (dissociative disorder not otherwise specified, dissociative amnesia, and depersonalization) have been reported in patients with panic disorder. [ 2 ] Depersonalization-derealization, which is often present in panic disorder, may be a manifestation of dissociative experiences. [ 3 ] Conversely, acute dissociation may be associated with symptoms of panic disorder.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 They showed a high level of dissociation too. 19 , 20 Nevertheless, during psychotherapy, they typically start to recognize several triggers of panic attacks, which are connected with stressful inner experiences and thoughts. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%